The reflection of national cognition in the historical story "Genghis Khan and his time" by M. Magauin (Eurasian Journal of Philology Science and Education, 2024)
The article reviews the first book of M. Magauin's documentary historical story "Genghis Khan and his time" and analyzes common situations in Turkic cognition. In particular, the history and culture of the nation, the personality of the leader of the nation, his place in history are analyzed, and the study of genealogical channels by the writer is proved by examples.In the personality of Genghis Khan, the qualities of heroism, intelligence, foresight, and bravery are revealed. It is analyzed that such a quality in the head of the ruler led him to recognize various intricacies of ruling the country. The article focuses on documentary-cognitive and philosophical works related to the person analyzed in detail and compared with people in the history of the world. One of the most important issues is creating a personal image of the great commander, his military heroism, and his artistic image as a citizen. The fundamental researches of many scientists on the spirituality of the nation and the place of the commander are favorably reflected. The writer's mastery of historical themes, methods of turning life's reality into artistic reality, creative aspects of their realization are comprehensively analyzed. The meaning of the word in the text, time continuity, and thought sequence are studied through the image of the character, the scenes of the time. Moreover, the techniques the author used in order to find out the national identity in the writer's works, the depiction of the national cognition are shown. The story explores the skills of the writer in creating national interests, awakening consciousness, and national character.Key words: national code, national consciousness, cognition, culture, personality.